2020
DOI: 10.31234/osf.io/n6gqx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

mixtur: An R package for designing, analysing, and modelling continuous report visual short-term memory studies

Abstract: Visual short-term memory (vSTM) is often measured via continuous-report tasks whereby participants are presented with stimuli that vary along a continuous dimension (e.g., colour) with the goal of memorising the stimuli features. At test, participants are probed to recall the feature value of one of the memoranda in a continuous manner (e.g., by clicking on a colour wheel). The angular deviation between the participant response and the true feature value provides an estimate of recall---and hence, vSTM---preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The relative proportion of the non-target (i.e., interfering item) distribution was estimated separately for each participant and condition (i.e., interference type and temporal predictability). The mixture modelling analysis was performed using the ‘mixtur’ package (version 1.0.0; Grange & Moore, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The relative proportion of the non-target (i.e., interfering item) distribution was estimated separately for each participant and condition (i.e., interference type and temporal predictability). The mixture modelling analysis was performed using the ‘mixtur’ package (version 1.0.0; Grange & Moore, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Until recently, most researchers have used custom-built code to implement the existing mixture models. Although there is software that implements some of these measurement models (e.g., Grange et al, 2021), this software mostly uses a two-step procedure. First, the parameters of the model are estimated separately for each subject in each condition using maximum likelihood methods.…”
Section: Benefits Of Hierarchical Bayesian Parameter Estimation Over ...mentioning
confidence: 99%
“…These methods constrain parameter estimation in several ways and can either lead to the over-or underestimation of standard errors in statistical tests (Boehm et al, 2018;Skrondal & Laake, 2001). Furthermore, to obtain robust parameter estimates maximum likelihood estimation requires at least 200 trials per subject per condition (Grange et al, 2021).…”
Section: Benefits Of Hierarchical Bayesian Parameter Estimation Over ...mentioning
confidence: 99%
“…Subsequent studies reported experiments that provide further evidence for the involvement of the sensory visual cortex in VSTM encoding using more sensitive statistical methods, such as mixture models (see Grange et al, 2021). Koivisto et al (2017) conducted two experiments to investigate whether TMS affects precision or guessing rates in a VSTM task, and whether these are affected dichotomously ('all or nothing') or gradually.…”
Section: Systematic Reviewmentioning
confidence: 99%